Biodegradable Polylactide Supraparticle Powders with Functional Additives for Biomedical Additive Manufacturing. (10th July 2022) - Canziani, Herbert; Hanschmann, Benedikt; Tischer, Florentin; Sommereyns, Alexander; Distler, Thomas; Schramm, Jonas; Hesse, Nicolas; Schmidt, Jochen; Grünewald, Alina; Detsch, Rainer; Boccaccini, Aldo; Maskos, Michael; et al.
Abstract: Additive manufacturing, in particular powder bed‐based fabrication processes hold promise to revolutionize biomedical engineering for the ability to provide customized, functional implants, for example as bone replacement materials. However, providing functional powder particles that unify material requirements for biodegradable and bioactive biomaterials and process requirements to enable successful powder bed fusion remains an unmet challenge. Here, a supraparticle‐based approach to create biodegradable poly(lactic acid) and composite powders for the additive manufacturing of bone replacement materials is introduced. Colloidal binary Ca‐SiO2 glasses and hydroxyapatite are incorporated as bioactive functional additives to support the formation of bone‐like calcium phosphate. The supraparticle powders are prepared by a scalable spray‐drying process, which offers control of particle size, shape, and composition. All process‐relevant powder characteristics are analyzed as a function of composition and structure, including flowability, thermal, and melt rheological properties. The optimized supraparticle powders are successfully used in the process of laser powder bed fusion of polymers to prepare macroscopic specimens via additive manufacturing. It is demonstrated that the material combination of the composites provides relevant functional properties, including biodegradation and bioactivity. The process provides a flexible and adjustable toolbox for the design of functional powders toward biomedical additive manufacturing. Abstract : Powder bed‐based additive manufacturing has gained increasing attention for biomedical applications such as bone grafting, where combinations of biodegradable polymers and functional, bioactive ceramics are of particular interest. Here, the fabrication, characterization, and additive manufacturing of customized polylactide (PLA) and PLA composite supraparticles into functional, macroscopic biomaterials is demonstrated.